Economic improvement and fish farming based on Smart Aquaculture Automatized System in Segobang Village, Banyuwangi - Arif Habib Fasya; Hapsari Kenconojati; Darmawan Setia Budi; Suciyono Suciyono; Maria Agustina Pardede; Dwi Retna Kumalaningrum; Prayogo Prayogo; Eka Saputra; Aji Akbar Firdaus; Muhammad Hilmy Maulana; Dewi Ambarwati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The fisheries and marine sector in East Java has abundant potential, one of which is Banyuwangi district. Banyuwangi Regency has potential in freshwater aquaculture because it has 324 rivers with an area of 735 km2 and swamps and reservoirs of 60 hectares. One of the villages in Banyuwangi Regency is Segobang Village, which has the potential to have abundant water sources and continuous flow. This potential can be utilized by training and assisting fish nurseries in Segobang Village by utilizing continuously flowing water and Smart Aquaculture Automatized System (SAAS) technology by utilizing biofilters and running water and aeration as a source of oxygen.  The stages carried out in this community service are as follows: initial assessment of the location, infrastructure and technology development, periodic training and mentoring, implementation and monitoring of the cultivation process, and continued marketing and sales. After the training, the Segobang Village community showed a significant increase in knowledge. The average pre-test scores ranged from 30 to 51, while the post-test scores increased to 79 to 87. This improvement shows that participants better understand the SAAS and its use in fish farming. Continued training and practice can help strengthen the adoption of this technology in the community.